Pendampingan Pemanfaatan Taman Dengan Tanaman Obat Keluarga Di Madrasah Diniyah Nurul Huda Dusun Tegalsari Desa Gerih Kabupaten Ngawi - Maya Wahyu; Febri Andika; Makno Wahyu Jajar Pangingal; Azis Fathul Hasan; Latifatus Sufiyah; Rela Mar’ati (Jurnal Abdikarya Pembangunan, 2023)
The objective Utilization of "TOGA Park" at Madrasah Diniyah Nurul Huda Dusun Tegalsari is to provide information on the use of family medicinal plants for students at Madrasah Diniyah Nurul Huda as additional traditional health knowledge. The activity method we carry out is direct practice and question and answer. The target group for our mentoring activities is the students of Madrasah Diniyah Nurul Huda Tegalsari Hamlet. Some of the benefits of our activities are: First, improving the students' skills in managing the vacant madrasa yards so that they can function correctly. The second is the existence of a TOGA park, which will be used a lot for the results for them. The activity results show that the students living around the madrasa can learn the benefits of planting and caring for the TOGA garden. However, this activity still needs further training.